Eleições disruptivas : plebiscito do NO, de 1988, no Chile, e a campanha lula 2002 - Borenstein, Carlos Eduardo Bellini (2024)
This dissertation will analyze two electoral campaign cases: the No plebiscite, which took place in Chile in 1988, when General Augusto Pinochet's regime was defeated; and Lula's victorious campaign in Brazil in 2002. The objective is to demonstrate how changes in political strategy, language and aesthetics were fundamental to the success of these campaigns. We will seek to demonstrate, anchored in knowledge of communication and political science, how the No and Lula campaigns won over the unengaged portion of the electorate (1/3) in the face of this segment's distrust in adhering to political projects of change in the midst of the Lula campaign. fear promoted by your opponents. We will debate theories about electoral behavior, based on Converse (1960 and 1964), Popkin (1994), Castro (1994 and 2014), Downs (1999), Ferraz (2003) and Figueiredo (2008). We will also reflect on political marketing and public opinion, through Lasswell (1927), Lazarsfeld (1944), Hohlfeldt (2001), Séguéla (2006), Lippmann (2008), Habermas (2013) and Corbellini (2018), showing that Contrary to what occurred after the emergence of rational choice theory (1999), emotion has a relevant influence on the decision-making process in electoral processes. The methodology used will be contente analysis, by Laurence Bardin (2011).